The Fruit Fly Lure CeraTrap: An Effective Tool for the Study of the Arboreal Ant Fauna (Hymenoptera: Formicidae). Issue 4 (22nd August 2018) - García-Martínez, Miguel A; Presa-Parra, Ehdibaldo; Valenzuela-González, Jorge E; Lasa, Rodrigo
Abstract: Despite preliminary reports of ants trapped in food-baited fruit fly traps, little is known regarding the identity of the myrmecofauna that can be sampled using this technique. This study aimed to examine the inventory completeness, activity and species occurrence of canopy ant assemblages collected in baited traps used for monitoring fruit flies in different fruit orchards in central Veracruz, Mexico. The trap models used in the sampling were Multilure, McPhail glass, and 500 ml blue polyethylene bottles. Three commercial fruit fly food attractants (CeraTrap, Captor + Borax, and BioLure) and two grape juice products (Jumex grape juice and Tang) were used as baits for sampling. In total 3, 626 ant workers belonging to 54 species, 19 genera, 10 tribes, and 5 subfamilies were collected. Among the five food attractants used in this study, CeraTrap recorded a markedly higher inventory completeness, ant activity and species occurrence per trap. This study reports for the first time the use of CeraTrap, as a promising and effective food attractant for collecting the foraging ants in the canopy of agroecosystems, which may be applicable to other habitats such as natural forests, mangroves, or agricultural settings such as coffee plantations.